Хронотоп у романі Валер’яна Підмогильного «Місто» - Бібік, В. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the peculiarities of chronotope formed in Valerian Pidmohylny’s novel «Misto». The main attention is given to the characteristics of the socio-historical chronotope; the significance of the chronotope of the road in the spatio-temporal organisation of the novel is analysed; the interdependency of external and internal space is established.